Testing the predictive power of an instrument titled "Orientation to School Renewal". Issue 4 (1st October 2020) - Shen, Jianping; Ma, Xin; Mansberger, Nancy; Gao, Xingyuan; Palmer, Louann Bierlein; Burt, Walter; Leneway, Robert; McCrumb, Dennis; Poppink, Sue; Reeves, Patricia; Whitten, Elizabeth
ABSTRACT: Policy makers, school practitioners, and scholars around the world have been searching for better school improvement models. The purpose of this study was to understand how an instrument we developed, Orientation to School Renewal, can be used to predict school-level academic achievement. We used the instrument to predict the academic performance of 83 schools as measured by the Michigan Student Test of Educational Progress (M-STEP) and the Scholastic Achievement Test (SAT) for mathematics and language. We found our instrument was more sensitive to M-STEP. We found that school renewal efforts were able to predict school academic performance with M-STEP in both mathematics and language. The three leading dimensions for predicting achievement on M-STEP were (a) focus on students and their achievement, (b) internal responsibility, and (c) continuous improvement. The renewal model provides a new perspective on school improvement, and future studies in other countries and international settings are recommended.